The Expansionist Politics of Sultan Agung and Turning Away the Sea in the 17th Century: Rereading Javanese Historiography - Miftahuddin; Ajat Sudrajat; Danar Widiyanta; Ita Mutiara Dewi; Kuncoro Hadi; Raymizard Alifian Firmansyah (Paramita: Historical Studies Journal, 2025)
Abstract: This article develops a thesis by Adrian B. Lapian and contextualizes the Islamic rule in Java that stimulated the movement of the sea people to turn their backs on the sea. It critiques conventional historiography that focuses only on heroic stories. Using critical maritime history studies, this article presents a re-reading of the political narrative of Sultan Agung's expansion into North and East Java. The history of Java is not only about political power and conflicts between Javanese kingdoms in the 17th century, but also about expansion, social problems, socio-political domination, and the erasure of collective memory of maritime culture. Therefore, this research attempts to write history with an alternative perspective to examine the "movement towards the sea" in Java, which has implications for the formation of an agrarian society. As a result of strengthening the legitimacy of royal power in the 16th-17th centuries, various violent incidents occurred in northern and peripheral Java. Under the pretext of expanding power and attempting to attack Batavia, this event was normalized, which becomes a phenomenon of historiographical problems in writing history, particularly regarding the minimal discussion about the oppression of the Javanese Maritime community under the political domination of Mataram (Sultan Agung).   Abstrak: Artikel ini, dengan mengembangkan tesis dari Adrian B. Lapian, membahas tentang kekuasaan Islam di Jawa yang menstimulasi gerak orang laut untuk memunggungi laut. Artikel ini juga bagian dari kritik terhadap historiografi konvensional yang hanya membahas tentang kisah-kisah heroik semata. Dengan menggunakan kajian sejarah maritim kritis, maka artikel ini menyajikan pembacaan ulang mengenai narasi politik ekspansi Sultan Agung ke daerah Jawa Utara dan Jawa Timur. Sejarah Jawa kenyataannya tidak hanya soal kekuasaan politik dan konflik politik kerajaan-kerajaan Jawa abad 17, tetapi juga soal ekspansi, masalah sosial, dominasi sosial-politik, sampai dengan penghapusan memori kolektif budaya maritim. Untuk itu, penelitian ini adalah bagian dari upaya penulisan sejarah dengan perspektif alternatif untuk melihat “gerak memunggungi laut” di Jawa, yang implikasinya berpengaruh terhadap terbentuknya masyarakat agraris. Akibat peneguhan legitimasi kuasa keraton, pada abad ke 16-17, di Jawa bagian utara dan pinggiran terjadi berbagai peristiwa yang penuh kekerasan. Dengan dalih perluasaan kekuasaan dan upaya penyerangan terhadap Batavia, membuat peristiwa ini dinormalisasi. Hal ini menjadi fenomena permasalahan historiografis dalam penulisan sejarah. Terutama, terkait pembahasan yang minim tentang ketertindasan masyarakat Maritim Jawa atas dominasi politik Mataram (Sultan Agung).